Максимізація запасу енергії у об’єктах космічної техніки - Байсков, М.Ф.; Будьонний, О.В.; Дзюба, Є.Д.; Коваленко, Є.Ю.; Прокопець, М.А. (Технічна електродинаміка, 2014)
Представлено розроблений алгоритм максимізації запасу енергії супутників на основі методу невизначених коефіцієнтів Лагранжа, який дозволяє розрахувати таку циклограму роботи, яка забезпечуватиме мінімальні втрати енергії. Наведено принципи формування виразу максимізації та системи обмежень. Показано результати оцінки запропонованого алгоритму на супутнику КПІ POLYTAN-1. В статье представлен разработанный алгоритм максимизации запаса энергии спутников на основе метода неопределенных коэффициентов Лагранжа, который позволяет рассчитать такую циклограмму работы, которая будет обеспечивать минимальные потери энергии. Приведены принципы формирования выражения максимизации и системы ограничений. Показаны результаты оценки предложенного алгоритма на спутнике КПИ POLYTAN-1. This paper presents an algorithm, designed to maximize the energy reserve of satellites, based on the method of Lagrange multipliers, which allows calculating a timeline that will ensure the minimum energy loss. Given the classification for subsystems - members of energy balance, their approximate timelines and features of their including in the algorithm. Shown the principles of formation for maximizing expression and system limitations. Showing results for assessing the proposed algorithm on the satellite KPI POLYTAN-1.